Internal structure of the Childhood and Primary School Violence Assessment Questionnaire - José González-Tovar; Alicia Hernández-Montaño; Diana I. López-Rodriguez; Martín C. Hernández-Ruíz (Interacciones)
The objective of this study is to validate the internal structure of the School Violence Evaluation Questionnaire in Children and Primary in a sample of northeastern Mexico. It is a quantitative and transversal study. A total of 733 children were included, of which 49.8% are men, 50.2% women, through intentional sampling, obtained from 78 basic education institutions in the city of Saltillo, Coahuila, Mexico. The average age was 12 years. The results confirmed a factorial structure of three dimensions that measure situations witnessed, lived and carried out. The instrument was reduced to 27 indicators of these dimensions, conserving the reliability obtained in previous studies. The contribution of the study is validation of the internal structure of the evaluation tool that allows the identification of school bullying and perceived damage and its characteristics, avoiding mainly the underestimation and normalization of violence.